The Use of Dubbing in Pronunciation Practice Class: Teachers’ and Students’ Perceptions - Akila, Ni Luh Ayu Ada; Listyani, Listyani; Nandari, Martha (Prominent, 2024)
Pronunciation is one of the important skills that language learners need to master. In consequence, their acquisition in language learning can be affected if they do not master the skills. However, one of the difficulties that students often face is related to pronunciation skills. This study attempted to investigate the English Language Education Program (ELEP) students' and teachers' perceptions of the use of the dubbing project in the Pronunciation Practice class. The study was conducted in Semester II, 2021-2022 academic year, at the English Language Education Program (ELEP), Faculty of Language and Arts (FLA), at a private university in Indonesia. The respondents of the research consisted of 26 (twenty-six) students, one speaking teacher, and one pronunciation teacher at the mentioned-above study program. In collecting the data, the researchers used a questionnaire and interview protocols. The research findings from the questionnaire and interview sessions revealed that the students and teachers showed positive attitudes toward the dubbing project. Most of the participants agreed that the project helps increase students' pronunciation skills, including syllables, word stresses, vowel and consonant sounds, intonation, and fluency. It can be concluded that the implementation of the dubbing project in the Pronunciation Practice class has beneficial impacts in improving students' pronunciation skills.